Validation of a teacher mathematics knowledge scale based on the Ernest framework among Malaysian teachers - Md Ghazali, Nor Hasnida; Zaini, Syaza Hazwani; Hamzah, Mahizer; Bakar, Noor Insyiraah Abu; imami, Muh Khairul Wajedi (International Journal of Evaluation and Research in Education (IJERE), 2024)
The aim of the current research was to validate the Malaysian version of the mathematical knowledge scale based on the Ernest framework. The participants include 100 teachers from Kelantan, Malaysia. An exploratory factor analysis (EFA) with principal components analysis and varimax rotation was conducted. This research determines the number of factors through eigenvalues greater than one and frames the structure of the scale through factor loading. The value of the eigenvalue and factor loading are considered in this research to frame and develop the structure of the scale. Furthermore, the reliability of the scale was tested with Cronbach’s alpha. The results showed six factors on the scale explaining 67.39% of the variances. A total of 26 items with factor loading greater than 0.60 were determined for the scale. The structure of the scale was as three items in the first factor, two items in the second factor, five items in the third factor, four items in the fourth factor, 10 items in the fifth factor, and two items in the sixth factor. Furthermore, the reliability of the scale was 0.958. This research concluded that the scale was internally consistent in measuring the teacher’s mathematics knowledge.